2017
DOI: 10.1002/jcph.1023
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacodynamic Analysis of Uric Acid–Lowering Effects of Febuxostat Based on Electronic Medical Records in Two Hospitals

Abstract: The aim of this study was to develop a population pharmacodynamic (PPD) model to describe uric acid (UA)-lowering effects in patients treated with febuxostat based on electronic medical records in 2 independent hospitals (university and city hospitals). Interhospital differences in the PPD model were also evaluated. We conducted the following 2 approaches to build the PPD models. A PPD model was developed separately using individual hospital data, and structural models and covariates between the two hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Of those that did subset reported drugs, they were typically sub-selected by certain drug types, such as statins, triptans, PPIs, and nasal steroids in one study, α1‐adrenoceptor antagonists in another, and antihypertensive calcium channel blockers in a third. Of the 33 studies reviewed, only five reported results focused on a single drug, metformin in the case of Xu et al 18 , febuxostat in the case of Muraki et al 48 , terbutaline sulfate in the case of Paik et al 27 , Fluoxetine in the case of Bi et al 45 , and Dextromethorphan in the case of Cummings et al 49 . Intuitively, this finding makes sense as most methods are focused on presenting candidates for further screening rather than having a pre-existing drug that should be further studied, and as such methods would result in a selection of candidates that should then be cross-validated against known clinical indications for method validity, rather than a clinical validation of an individual drug itself selected from said list of candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Of those that did subset reported drugs, they were typically sub-selected by certain drug types, such as statins, triptans, PPIs, and nasal steroids in one study, α1‐adrenoceptor antagonists in another, and antihypertensive calcium channel blockers in a third. Of the 33 studies reviewed, only five reported results focused on a single drug, metformin in the case of Xu et al 18 , febuxostat in the case of Muraki et al 48 , terbutaline sulfate in the case of Paik et al 27 , Fluoxetine in the case of Bi et al 45 , and Dextromethorphan in the case of Cummings et al 49 . Intuitively, this finding makes sense as most methods are focused on presenting candidates for further screening rather than having a pre-existing drug that should be further studied, and as such methods would result in a selection of candidates that should then be cross-validated against known clinical indications for method validity, rather than a clinical validation of an individual drug itself selected from said list of candidates.…”
Section: Resultsmentioning
confidence: 99%
“…18 Electronic medical records, which include routinely collected longitudinal clinical care data are increasingly used for clinical research and optimizing therapeutics. [19][20][21][22] A combination of real-world data and quantitative model-based approaches will enable conversion of the empirical evidence to usable and actionable knowledge that can potentially lead to improvements in NOWS-related patient care.…”
mentioning
confidence: 99%
“…Additionally, given that there are several barriers to performing clinical pharmacokinetic studies in pediatrics, utilizing real‐world data from electronic medical records from hospitals to generate real‐world evidence could lead to improved care in the pediatric population 18 . Electronic medical records, which include routinely collected longitudinal clinical care data are increasingly used for clinical research and optimizing therapeutics 19–22 . A combination of real‐world data and quantitative model‐based approaches will enable conversion of the empirical evidence to usable and actionable knowledge that can potentially lead to improvements in NOWS‐related patient care.…”
mentioning
confidence: 99%